FROM EXPERT TO EPISTEMIC COMMUNITIES: ON THE TRANSFORMATION OF INSTITUTIONAL FRAMES OF POWER IN THE MODERN WORLD (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The article deals with the phenomenon of epistemic communities. The concept was coined by P. Haas in the late XX century in an attempt to analyze functions and political prospects of expert and professional knowledge in the modern knowledge-based society. The concept has been widely used during the recent decades in sociology of knowledge, policy studies and social philosophy. Despite the fact that some scholars voiced a number of critical remarks, no (or very few) attempts to rethink the concept of epistemic communities have been made. The article gives a review of research into epistemic communities and introduces the concept of epistemic operating mode in order to rethink the concept and clear up operational mechanisms of epistemic communities as a specific form of knowledge (expert) communities.